Geneza, przebieg i skutki działań wojennych w województwie wołyńskim we wrześniu 1939 roku - Włodarkiewicz, Wojciech; Vlodarkevich, V. (Волинський національний університет імені Лесі Українки, 2012)
Województwo wołyńskie odgrywało ważną rolę w polskim planie operacyjnym «Wschód», a w razie wojny z Niemcami miało stanowić jedynie zaplecze frontu. Od 7 września przejściowo przebywały w nim polskie naczelne władze państwowe i wojskowe. Od 14 do 16 września IV Dywizja Lekka Wehrmachtu bezskutecznie usiłowała zdobyć Uściług i Włodzimierz. 17 września 1939 r. rozpoczęła się agresja ZSRR na Polskę, Wojsko Polskie nie zorganizowało obrony, natomiast opór stawił Korpus Ochrony Pogranicza. Ostatecznie do 23 września Armia Czerwona opanowała całe województwo wołyńskie.Volhynian province played very important role in Polish operating plan called «East» and, in the case of the war with Germany, it was supposed to be only the back of the front. From 17th September, for some time, Polish principal authority of the state and military stationed there. From 14th to 16th September 4th Light Division Wehrmacht without success tried to conquer Uściług and Włodzimierz. On 17th September 1939 the aggression of the USRR on Poland started. The Polish Army did not organise any defence, whereas Border Protection Corps resisted. Finally, till 23rd September the Red Army took control over the whole Volhynian province.
The Genesis, the Process and the Results of Military Actions in Volhynian Province in September 1939